Arcadian America the death and life of an environmental tradition - Sachs, Aaron (Yale University Press, 2013)
"Perhaps America's best environmental idea was not the national park but the garden cemetery, a use of space that quickly gained popularity in the mid-nineteenth century. Such spaces of repose brought key elements of the countryside into rapidly expanding cities, making nature accessible to all and serving to remind visitors of the natural cycles of life. In this unique interdisciplinary blend of historical narrative, cultural criticism, and poignant memoir, Aaron Sachs argues that American cemeteries embody a forgotten landscape tradition that has much to teach us in our current moment of environmental crisis. Until the trauma of the Civil War, many Americans sought to shape society into what they thought of as an Arcadia--not an Eden where fruit simply fell off the tree, but a public garden that depended on an ethic of communal care, and whose sense of beauty and repose related directly to an acknowledgment of mortality and limitation. Sachs explores the notion of Arcadia in the works of nineteenth-century nature writers, novelists, painters, horticulturists, landscape architects, and city planners, and holds up for comparison the twenty-first century's--and his own--tendency toward denial of both death and environmental limits. His far-reaching insights suggest new possibilities for the environmental movement today and new ways of understanding American history."--Jacket
Description based on print version record and online resource (A&AePortal, viewed on September 14, 2023)
Keywords: 1800-1899; American literature; Arcadia in art; Arcadia in literature; Cemeteries; Environmental responsibility; Environmentalism / Social aspects; Human ecology; American literature / 19th century / History and criticism; Cemeteries / Environmental aspects / United States; Cemeteries / Social aspects / United States; Cemeteries / United States / History / 19th century; Environmental responsibility / United States; Environmentalism / Social aspects / United States; Human ecology / United States / History / 19th century; Landschaftsgarten; Friedhof; Umweltbewusstsein; USA